Biomechanical study of hammer head speed and handle motion of different record levels - Fujii, H.; Ohyama-Byun, K.; Fujii, N. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
The purpose of this study was to investigate the difference of leading distance of handle and handle movement between competitors of different record levels during turn phases, and body movement to obtain the leading distance of handle. Forty-four male throwers (throwing record: 80.50-44.17m) participated in the study. Throwing motions were videotaped on high-speed VTR cameras, and three-dimensional coordinates were calculated using a DLT method. Kinematic parameters were calculated such as the hammer head speed, the leading distance of handle, the handle velocity and velocity of midpoint of both shoulder joints in the rotating plane coordinate system where Xicr is the hammer head speed direction and Yicr is the direction connecting the hammer head and the instantaneous rotation center. Further, we investigated the difference in the calculation parameters between Excellent group n=18?74.77±4.30m and Normal group (n=26, 55.80±5.96m). Fundamental factors were summarized as follows: (1) There was no significant difference between competitors of different record levels in the magnitude of leading distance of handle. Excellent group showed a higher value of handle velocity in the Xicr direction than Normal group during turn phase. (2) Handle velocity in the Yicr direction was mainly obtained by increasing the velocity of midpoint of both shoulder joints due to the trunk back lean during double support phase (DSP). Since the increase and decrease of leading distance of handle is consistent with the increase and decrease of handle velocity in the Yicr direction, Back lean of trunk may increase leading distance of handle. In addition, the generation of the handle velocity in the Xicr direction was mainly the speed generated by rotational movement of the body.